A method for characterizing density distribution of cemented carbide blanks
By adding alumina powder to the cemented carbide mixture and sintering treatment, the problem of difficult to characterize the density distribution of cemented carbide blanks is solved, and effective characterization of density distribution and improvement of the qualification rate of cemented carbide blanks is achieved.
Patent Information
- Application Number
- CN202411114929.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The prior art lacks effective methods for characterizing the density distribution of cemented carbide blanks.
After ball milling and drying by adding alumina powder to the cemented carbide mixture, the cemented carbide blank was pressed and sintered. The cemented carbide blank was then cut along the central cross-section and the distribution of alumina was observed using a low-power microscope to characterize the density distribution.
The effective characterization of the density distribution of cemented carbide blanks is achieved, with simple operation and controllable cost, and the pass rate of cemented carbide blanks is improved by adjusting production process parameters.
Smart Images

Figure CN118641424B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide performance detection, and in particular relates to a method for characterizing density distribution of a cemented carbide blank. Background Art
[0002] Cemented carbide blanks are composite materials made of refractory metal hard compounds and bonding metals or alloys by powder metallurgy. The production process is: wet grinding and spraying the various component powders of cemented carbide into a mixture, then pressing the mixture into a compact, and finally sintering the compact at high temperature. The blanks manufactured by the above production process are cemented carbide blanks, which are also cemented carbide without various processing and post-treatment.
[0003] The appearance, dimensional tolerance, unit weight, density distribution, etc. of cemented carbide blanks are the key to quality control of cemented carbide blanks. Cemented carbide blanks with qualified appearance, dimensional tolerance, unit weight, density distribution, etc. are the prerequisite for producing high-quality cemented carbide products. The quality of cemented carbide blanks determines the performance, organizational structure and processing difficulty of cemented carbide, so the quality of cemented carbide blanks must be guaranteed. If the product quality of cemented carbide blanks needs to be improved, the appearance, dimensional tolerance, unit weight, density distribution, etc. of cemented carbide blanks are the key points that must be characterized and displayed, so as to facilitate subsequent testing and achieve complete quality control of cemented carbide blanks.
[0004] The density distribution of cemented carbide blanks is different from their appearance, dimensional tolerance and unit weight. The appearance can be inspected by an optical microscope or a special appearance inspection scanning device, the dimensional tolerance can be measured by various measuring tools, and the unit weight can be measured by a high-precision weight measuring instrument. However, there is currently no universal and intuitive characterization method for the density distribution of cemented carbide blanks on the market. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a method for characterizing the density distribution of cemented carbide blanks.
[0006] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0007] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0008] S1. Take a cemented carbide mixture and alumina powder, add alcohol and perform ball milling to obtain a slurry, and dry the slurry to obtain a uniform powder;
[0009] S2, according to the size and shape requirements of the cemented carbide blank, uniformly filling the uniform powder into the mold cavity of a press for pressing the cemented carbide blank, and pressing to obtain the cemented carbide blank;
[0010] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0011] S4. Cut the cemented carbide blank along the central cross section, and use a low-power microscope to observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank to characterize the density distribution of the cemented carbide blank.
[0012] As a preferred embodiment of the method for characterizing the density distribution of cemented carbide blanks described in the present invention, it also includes step S5, which adjusts the production process parameters including the pressing method and increasing the forming pressure through the characterization of the density distribution of the cemented carbide blanks to improve the qualified rate of the cemented carbide blanks.
[0013] As a preferred embodiment of the method for characterizing density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, the mass ratio of cemented carbide mixture to alumina powder is 100:(1-2).
[0014] As a preferred embodiment of the method for characterizing the density distribution of cemented carbide blanks described in the present invention, in the step S1, the mass of the added alcohol is 3 to 4 times the mass of the cemented carbide mixture and the alumina powder.
[0015] As a preferred embodiment of the method for characterizing the density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, alumina is vacuum calcined at 1500-1600°C for 2-4 hours, and after the calcination is completed, alumina powder with a particle size of 200-400 mesh is sieved to obtain.
[0016] As a preferred embodiment of the method for characterizing the density distribution of cemented carbide blanks described in the present invention, in the step S1, the amount of cemented carbide mixture added is calculated based on the volume of the cemented carbide blank to be prepared, the shrinkage coefficient during sintering (obtained based on previous production data) and the density of the cemented carbide mixture.
[0017] As a preferred embodiment of the method for characterizing density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, the ambient temperature when taking the cemented carbide mixture is 20-50°C, and the ambient humidity is 20-50%.
[0018] As a preferred embodiment of the method for characterizing density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, the ball milling speed is 33-44 r / min, and the ball milling time is 1-3 h.
[0019] As a preferred embodiment of the method for characterizing density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, the drying temperature is 80-90°C.
[0020] As a preferred embodiment of the method for characterizing the density distribution of cemented carbide blanks described in the present invention, wherein: in the step S1, after drying is completed, the agglomerated part of the dried powder is gently crushed using an experimental metal spoon, and the mixing and crushing is stopped after all the powder is mixed and crushed into a uniform powder.
[0021] As a preferred embodiment of the method for characterizing density distribution of cemented carbide blanks described in the present invention, wherein: in the step S2, the pressing is unidirectional pressing or bidirectional pressing.
[0022] The beneficial effects of the present invention are as follows:
[0023] The present invention provides a method for characterizing the density distribution of a cemented carbide blank. The method comprises the following steps: adding alumina powder to a cemented carbide mixture to obtain a uniform powder after wet grinding and drying, pressing the powder into a cemented carbide blank, and sintering the powder to obtain a cemented carbide blank in which alumina can be observed through a low-power microscope. During the sintering of the cemented carbide blank, the alumina powder will not react with tungsten carbide and cobalt, will not undergo chemical reactions to produce new substances, and will not melt at the sintering temperature. The distribution of alumina is proportional to the density distribution of the cemented carbide blank. The distribution of alumina can be used to characterize the density distribution of the cemented carbide blank. The implementation is simple and the cost is controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0025] Figure 1 This is a photograph of the cut surface of the cemented carbide blank prepared in Example 1 of the present invention.
[0026] Figure 2 This is a photograph of the cut surface of the cemented carbide blank prepared in Example 2 of the present invention.
[0027] Figure 3 This is a photograph of the cut surface of the cemented carbide blank prepared in Example 3 of the present invention.
[0028] Figure 4 This is a photograph of the cut surface of the cemented carbide blank prepared in Example 4 of the present invention.
[0029] Figure 5This is a photograph of the cut surface of the cemented carbide blank prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention provides a method for characterizing the density distribution of a cemented carbide blank, and adopts aluminum oxide as a "tracer" to characterize the density distribution of the cemented carbide blank.
[0032] Alumina is a white solid powder with the advantage of a high melting point of 2054°C and high chemical stability. The main components of cemented carbide compacts are tungsten carbide and cobalt, and the temperature for sintering cemented carbide is about 1450°C. Alumina powder is added to the cemented carbide mixture and pressed into a cemented carbide compact. During the sintering process of the cemented carbide compact, the alumina powder will not react with tungsten carbide and cobalt, will not undergo chemical reactions to produce new substances, and will not melt at this temperature. After sintering, the cemented carbide compact will become a dense alloy with a tissue structure, and the alumina will be densely surrounded by its tissue structure. Its position and shape can be seen after cutting the surface.
[0033] Alumina powder is vacuum calcined at 1500~1600℃ for 2-4 hours. After calcination, impurities on the surface of alumina powder can be removed to improve the purity of alumina. When added to cemented carbide mixture, other impurities will not be mixed in, avoiding the reaction between impurities and mixture to produce other effects.
[0034] Alumina powder is sieved on a sieve to obtain fine alumina powder of appropriate size with a particle size of 200-400 mesh, and 1-2% alumina powder relative to the cemented carbide mixture is added. The alumina powder and the cemented carbide mixture are ball-milled, dried, and the uniform powder obtained by mixing and grinding is pressed into a cemented carbide compact. During the pressing process, because the alumina powder is mixed with the cemented carbide mixture components and does not react with the mixture, the position and distribution of the fine alumina powder in the compact is only related to factors that affect the density distribution of the compact, such as the pressing force and the mold structure.
[0035] During the sintering process of the pressed blank, the alumina powder will not react with tungsten carbide and cobalt, and will not change its position and particle size. After sintering, the cemented carbide blank is cut open, and the cut surface of the prepared cemented carbide blank is observed using a low-power microscope. It can be seen that the alumina on the cut surface is of appropriate size and density, and is suitable for observation. Through the distribution of alumina particles, it is proportional to the density distribution of the cemented carbide blank, that is, where the pores are dense, the density of the cemented carbide blank is better, and where the pores are not concentrated, the density of the cemented carbide blank is worse, so the density distribution of the cemented carbide blank can be characterized, and the parts with good and poor density of the cemented carbide blank can be observed. Through the density distribution of the cemented carbide blank characterized, the production process parameters can be adjusted to improve the qualified rate of the cemented carbide blank.
[0036] According to one aspect of the present invention, the present invention provides the following technical solution:
[0037] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0038] S1, take cemented carbide mixture and alumina powder, add alcohol and then ball-mill to obtain slurry, and dry the slurry to obtain uniform powder;
[0039] S2. According to the size and shape requirements of the cemented carbide blank, the uniform powder is evenly filled into the mold cavity of a press for pressing the cemented carbide blank, and the cemented carbide blank is obtained by pressing;
[0040] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0041] S4. Cut the cemented carbide blank along the central cross section, and use a low-power microscope to observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank to characterize the density distribution of the cemented carbide blank.
[0042] Preferably, the method further comprises step S5, adjusting production process parameters including pressing method and increasing forming pressure by characterizing the density distribution of the cemented carbide blank, so as to improve the qualified rate of the cemented carbide blank.
[0043] Preferably, in step S1, the mass ratio of the cemented carbide mixture to the alumina powder is 100:(1-2).
[0044] Preferably, in step S1, the mass of the added alcohol is 3 to 4 times the sum of the masses of the cemented carbide mixture and the alumina powder.
[0045] Preferably, in step S1, the alumina is calcined in vacuum at 1500-1600° C. for 2-4 hours, and after the calcination, the alumina powder with a particle size of 200-400 mesh is sieved to obtain the alumina powder.
[0046] Preferably, in step S1, the amount of cemented carbide mixture added is calculated based on the volume V of the cemented carbide blank to be prepared, the shrinkage coefficient S during sintering (obtained based on previous production data) and the density ρ of the cemented carbide mixture.
[0047] Preferably, in step S1, the ambient temperature when taking the cemented carbide mixture is 20-50° C., and the ambient humidity is 20-50%.
[0048] Preferably, in step S1, the ball milling speed is 33-44 r / min, and the ball milling time is 1-3 h.
[0049] Preferably, in step S1, the drying temperature is 80-90°C.
[0050] Preferably, in step S1, after drying is completed, the agglomerated parts of the dried powder are gently crushed using a laboratory metal spoon, and the mixing and crushing is stopped after all the powder is mixed and crushed into a uniform powder.
[0051] Preferably, in step S2, the pressing is unidirectional pressing or bidirectional pressing.
[0052] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0053] Example 1
[0054] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0055] S1. Take a cemented carbide mixture and alumina powder, add alcohol and perform ball milling to obtain a slurry, and dry the slurry to obtain a uniform powder;
[0056] Select a cemented carbide grade with a cobalt content of 25wt%, select a cemented carbide blank model of ⌀12mm×20mm, and calculate the single weight M of the mixture of a cemented carbide blank to be produced by the formula V×S×ρ R 31g. Weigh 31g of this grade of mixed material in the batching room. The ambient temperature is 27℃ and the humidity is 31%. The bag is sealed when taking the material. Alumina is vacuum calcined at 1550℃ for 2.5h. After calcination, the alumina powder is sieved to obtain alumina powder with a particle size of 200~400 mesh. According to the formula 1%×M R Calculate the required weight of aluminum oxide powder M Y0.31g, weigh 0.31g of 200-400 mesh alumina powder. Y +M R ) Calculate the weight of alcohol to be added to be 109.59g. Pour 31g of the mixed material, 0.31g of 200-400 mesh alumina powder and 109.59g of alcohol into the drum of the experimental small ball mill at the same time, seal the drum, start the experimental small ball mill, set the ball mill speed to 33r / min, and the ball milling time to 1.5h. After the ball milling is completed, take out the mixed slurry, collect it in a container and put it in a dryer for drying. The drying temperature is set to 80℃. After the drying is completed, use the experimental metal spoon to gently mix and crush the agglomerated part of the dried powder. Stop mixing and grinding after all the powder is mixed and ground into a uniform powder.
[0057] S2. According to the size and shape requirements of the cemented carbide blank, the uniform powder is evenly filled into the mold cavity of a press for pressing the cemented carbide blank, and the cemented carbide blank is obtained by pressing;
[0058] The powder is rolled into uniform fine powder, and is uniformly filled into the mold cavity of the press for pressing the cemented carbide blank according to the size and shape requirements of the ⌀12mm×20mm cemented carbide blank. The press is started, and a ⌀12mm×20mm cemented carbide blank using the prepared powder is pressed using a unidirectional pressing method.
[0059] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0060] S4. Cut the cemented carbide blank along the central cross section, place the cemented carbide blank with the compression surface facing downward, and observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank using a low-power microscope (a photo of the cut surface of the cemented carbide blank prepared in this embodiment is shown in FIG. Figure 1 As shown in the figure, it can be observed that the distribution of alumina in the middle area of the pressure surface close to the cut surface is denser, and the distribution of alumina in the middle area from the non-pressure surface to the cut surface is sparser than that in the middle area from the pressure surface to the cut surface, which is consistent with the theoretical density distribution of cemented carbide blanks produced by unidirectional pressing. The density of the pressure surface close to the middle area of the cut surface is better, and the density of the area from the non-pressure surface to the middle layer is worse than that from the pressure surface to the middle layer. The density distribution of cemented carbide blanks is characterized.
[0061] S5. By characterizing the density distribution of cemented carbide blanks, the production process parameters were adjusted and the unidirectional pressing method was changed to bidirectional pressing, which improved the density uniformity of the cemented carbide blanks, reduced the edge chipping and corner chipping of the non-pressure surface, reduced the processing rework and scrap volume of the cemented carbide blanks, and improved the qualified rate of cemented carbide blanks.
[0062] Example 2
[0063] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0064] S1, take cemented carbide mixture and alumina powder, add alcohol and then ball-mill to obtain slurry, and dry the slurry to obtain uniform powder;
[0065] Select a cemented carbide grade with a cobalt content of 25wt%, select a cemented carbide blank model of ⌀12mm×20mm, and calculate the single weight M of the mixture of a cemented carbide blank to be produced by the formula V×S×ρ R 31g. Weigh 31g of this grade of mixed material in the batching room. The ambient temperature is 28℃ and the humidity is 30%. The bag is sealed when taking the material. Alumina is vacuum calcined at 1550℃ for 2.5h. After calcination, the alumina powder is sieved to obtain alumina powder with a particle size of 200~400 mesh. According to the formula 1%×M R Calculate the required weight of aluminum oxide powder M Y 0.31g, weigh 0.31g of 200-400 mesh alumina powder. Y +M R ) Calculate the weight of alcohol to be added to be 109.59g. Pour 31g of the mixed material, 0.31g of 200-400 mesh alumina powder and 109.59g of alcohol into the drum of the experimental small ball mill at the same time, seal the drum, start the experimental small ball mill, set the ball mill speed to 33r / min, and the ball milling time to 1.5h. After the ball milling is completed, take out the mixed slurry, collect it in a container and put it in a dryer for drying. The drying temperature is set to 80℃. After the drying is completed, use the experimental metal spoon to gently mix and crush the agglomerated part of the dried powder. Stop mixing and grinding after all the powder is mixed and ground into a uniform powder.
[0066] S2. According to the size and shape requirements of the cemented carbide blank, the uniform powder is evenly filled into the mold cavity of a press for pressing the cemented carbide blank, and the cemented carbide blank is obtained by pressing;
[0067] The powder is mixed and rolled into uniform fine powder, and is uniformly filled into the mold cavity of the press for pressing the cemented carbide blank according to the size and shape requirements of the ⌀12mm×20mm cemented carbide blank. The press is started, and a ⌀12mm×20mm cemented carbide blank using the prepared powder is pressed using a bidirectional pressing method.
[0068] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0069] S4. Cut the cemented carbide blank along the central cross section, place the cemented carbide blank with the compression surface facing downward, and observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank using a low-power microscope (a photo of the cut surface of the cemented carbide blank prepared in this embodiment is shown in FIG. Figure 2 As shown in the figure, it can be observed that the aluminum oxide in the middle area of the cut surface is denser than in other areas, and the aluminum oxide in the part farther from the middle area is sparser, which is consistent with the theoretical density distribution of cemented carbide blanks produced by the bidirectional pressing method. The overall density is more uniform, and the density in the middle area is better than that in the areas on both sides. The density distribution of cemented carbide blanks is characterized.
[0070] S5. By characterizing the density distribution of cemented carbide blanks, the production process parameters were adjusted, the pressing top pressure was increased, the density of the two side areas was improved, the sintering deformation, processing rework and scrap volume of the cemented carbide blanks were reduced, and the qualified rate of cemented carbide blanks was improved.
[0071] Example 3
[0072] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0073] S1. Take a cemented carbide mixture and alumina powder, add alcohol and perform ball milling to obtain a slurry, and dry the slurry to obtain a uniform powder;
[0074] Select a cemented carbide grade with a cobalt content of 12wt%, select a cemented carbide blank model of ⌀12mm×20mm, and calculate the single weight M of the mixture of a cemented carbide blank to be produced by the formula V×S×ρ R 34g. Weigh 34g of this grade of mixed material in the batching room. The ambient temperature is 27℃ and the humidity is 28%. The bag is sealed when taking the material. Alumina is vacuum calcined at 1550℃ for 2.5h. After calcination, the alumina powder is sieved to obtain alumina powder with a particle size of 200~400 mesh. The formula 1%×M R Calculate the required weight of aluminum oxide powder M Y0.34g, weigh 0.34g of 200-400 mesh alumina powder. Y +M R ) Calculate the weight of alcohol to be added to be 120.19g, and pour 34g of the mixed material, 0.34g of 200-400 mesh alumina powder, and 120.19g of alcohol into the drum of the experimental small ball mill at the same time, seal the drum, start the experimental small ball mill, set the ball mill speed to 44r / min, and the ball milling time to 1.5h. After the ball milling is completed, take out the mixed slurry, collect it in a container and put it in a dryer for drying, and the drying temperature is set to 80℃. After the drying is completed, use the experimental metal spoon to gently mix and crush the agglomerated part of the dried material powder, and stop mixing and grinding after all the material powder is mixed and ground into a uniform powder.
[0075] S2, according to the size and shape requirements of the cemented carbide blank, uniformly filling the uniform powder into the mold cavity of a press for pressing the cemented carbide blank, and pressing to obtain the cemented carbide blank;
[0076] The powder is rolled into uniform fine powder, and is uniformly filled into the mold cavity of the press for pressing the cemented carbide blank according to the size and shape requirements of the ⌀12mm×20mm cemented carbide blank. The press is started, and a ⌀12mm×20mm cemented carbide blank using the prepared powder is pressed using a unidirectional pressing method.
[0077] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0078] S4. Cut the cemented carbide blank along the central cross section, place the cemented carbide blank with the compression surface facing downward, and observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank using a low-power microscope (a photo of the cut surface of the cemented carbide blank prepared in this embodiment is shown in FIG. Figure 3 As shown in the figure, it can be observed that the closer the part is to the pressure surface, the denser the alumina is, and the farther the part is from the pressure surface, the sparser the alumina is, which is consistent with the theoretical density distribution of cemented carbide blanks produced by unidirectional pressing. The closer the part is to the pressure surface, the better the density is, and the farther the part is from the pressure surface, the worse the density is. The density distribution of cemented carbide blanks is characterized.
[0079] S5. By characterizing the density distribution of cemented carbide blanks, the production process parameters were adjusted, and the unidirectional pressing method was changed to bidirectional pressing, and the pressure holding time was set to 8 seconds. This improved the density uniformity of the cemented carbide blanks, reduced the edge chipping and burrs at the edge of the non-pressure surface, reduced the amount of processing and repair and scrapping of cemented carbide blanks, and improved the qualified rate of cemented carbide blanks.
[0080] Example 4
[0081] A method for characterizing density distribution of cemented carbide blanks comprises the following steps:
[0082] S1. Take a cemented carbide mixture and alumina powder, add alcohol and perform ball milling to obtain a slurry, and dry the slurry to obtain a uniform powder;
[0083] Select a cemented carbide grade with a cobalt content of 12wt%, select a cemented carbide blank model of ⌀12mm×20mm, and calculate the single weight M of the mixture of a cemented carbide blank to be produced by the formula V×S×ρ R 34g. Weigh 34g of this grade of mixed material in the batching room. The ambient temperature is 26℃ and the humidity is 28%. The bag is sealed when taking the material. Alumina is vacuum calcined at 1550℃ for 2.5h. After calcination, the alumina powder is sieved to obtain alumina powder with a particle size of 200~400 mesh. According to the formula 1%×M R Calculate the required weight of aluminum oxide powder M Y 0.34g, weigh 0.34g of alumina powder under 200-400 mesh sieve. Y +M R ) Calculate the weight of alcohol to be added to be 120.19g. Pour 34g of the mixed material, 0.34g of alumina powder under a 200-400 mesh sieve, and 120.19g of alcohol into the drum of the experimental small ball mill at the same time, seal the drum, start the experimental small ball mill, set the ball mill speed to 40r / min, and the ball milling time to 1.5h. After the ball milling is completed, take out the mixed slurry, collect it in a container, and put it in a dryer for drying. The drying temperature is set to 80℃. After the drying is completed, use the experimental metal spoon to gently mix and crush the agglomerated part of the dried powder. Stop mixing and grinding after all the powder is mixed and ground into a uniform powder.
[0084] S2, according to the size and shape requirements of the cemented carbide blank, uniformly filling the uniform powder into the mold cavity of a press for pressing the cemented carbide blank, and pressing to obtain the cemented carbide blank;
[0085] The powder is mixed and rolled into uniform fine powder, and is uniformly filled into the mold cavity of the press for pressing the cemented carbide blank according to the size and shape requirements of the ⌀12mm×20mm cemented carbide blank. The press is started, and a ⌀12mm×20mm cemented carbide blank using the prepared powder is pressed using a bidirectional pressing method.
[0086] S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank, to obtain a cemented carbide blank in which aluminum oxide particles can be observed under a low-power microscope;
[0087] S4. Cut the cemented carbide blank along the central cross section, place the cemented carbide blank with the compression surface facing downward, and observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank using a low-power microscope (a photo of the cut surface of the cemented carbide blank prepared in this embodiment is shown in FIG. Figure 4 As shown in the figure, it can be observed that the aluminum oxide in the middle area of the cut surface is denser than in other areas, and the aluminum oxide in the part farther from the middle area is sparser, which is consistent with the theoretical density distribution of cemented carbide blanks produced by the bidirectional pressing method. The overall density is more uniform, and the density in the middle area is better than that in the areas on both sides. The density distribution of cemented carbide blanks is characterized.
[0088] S5. By characterizing the density distribution of cemented carbide blanks, the production process parameters were adjusted, the pressing top pressure was increased, the density of the two side areas was improved, the sintering deformation, processing rework and scrap volume of the cemented carbide blanks were reduced, and the qualified rate of the cemented carbide blanks was improved.
[0089] Comparative Example 1
[0090] The difference from Example 2 is that alumina powder with a particle size of ≤800 mesh is used in step S1.
[0091] The photo of the cut surface of the cemented carbide blank prepared in this comparative example is as follows Figure 5 As shown, the amount of aluminum oxide on the cut surface is relatively small, and it is impossible to determine the density of aluminum oxide and characterize the density distribution of the cemented carbide blank.
[0092] Comparative Example 2
[0093] The difference from Example 2 is that in step S1, the formula 0.5%×M R Calculate the required weight of aluminum oxide powder M Y It is 0.155g.
[0094] The amount of aluminum oxide in the middle area of the cut surface of the cemented carbide blank prepared in this comparative example is relatively small, while the amount of aluminum oxide in the edge part is larger. Most of the aluminum oxide is too large, making it impossible to determine the density of the aluminum oxide particles and characterize the density distribution of the cemented carbide blank.
[0095] Comparative Example 3
[0096] The difference from Example 2 is that chromium oxide powder is used instead of aluminum oxide powder.
[0097] There is no obvious pore on the open surface of this comparative example, and the porosity is A02 through metallographic detection, which cannot characterize the density distribution of the cemented carbide blank.
[0098] It can be seen from the above embodiments and comparative examples that the present invention adds alumina powder to the cemented carbide mixture to obtain a uniform powder after wet grinding and drying, and presses it into a cemented carbide blank, which is sintered to obtain a cemented carbide blank in which alumina can be observed through a low-power microscope. During the sintering process of the cemented carbide blank, the alumina powder will not react with tungsten carbide and cobalt, will not undergo chemical reactions to produce new substances, and will not melt at the sintering temperature. The distribution of alumina is proportional to the density distribution of the cemented carbide blank. The distribution of alumina can be used to characterize the density distribution of the cemented carbide blank. The implementation operation is simple and the cost is controllable.
[0099] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for characterizing density distribution of cemented carbide blanks, characterized in that: The steps include: S1. Take a cemented carbide mixture and alumina powder, add alcohol and then ball-mill to obtain a slurry, and then dry the slurry to obtain a uniform powder; the mass ratio of the cemented carbide mixture to the alumina powder is 100:(1-2); calcine the alumina at 1500-1600°C in vacuum for 2-4h, and after calcination, sieve to obtain alumina powder with a particle size of 200-400 mesh; S2, according to the size and shape requirements of the cemented carbide blank, uniformly filling the uniform powder into the mold cavity of a press for pressing the cemented carbide blank, and pressing to obtain the cemented carbide blank; S3, sintering the pressed cemented carbide blank according to the sintering process for producing the same grade of cemented carbide blank to obtain a cemented carbide blank; S4. Cut the cemented carbide blank along the central cross section, and use a low-power microscope to observe the distribution of aluminum oxide on the cut surface of the cemented carbide blank to characterize the density distribution of the cemented carbide blank.
2. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: The method further comprises step S5, wherein the production process parameters including the pressing method and increasing the forming pressure are adjusted based on the characterization of the density distribution of the cemented carbide blank, so as to improve the qualified rate of the cemented carbide blank.
3. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In the step S1, the mass of the added alcohol is 3 to 4 times the mass of the cemented carbide mixture and the alumina powder.
4. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In the step S1, the ambient temperature when taking the cemented carbide mixture is 20-50° C., and the ambient humidity is 20-50%.
5. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In the step S1, the ball milling speed is 33-44 r / min, and the ball milling time is 1-3 h.
6. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In step S1, the drying temperature is 80-90°C.
7. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In the step S1, after the drying is completed, the agglomerated part of the dried powder is gently crushed using a laboratory metal spoon, and the mixing and crushing is stopped after all the powder is mixed and crushed into a uniform powder.
8. The method for characterizing density distribution of cemented carbide blank according to claim 1, characterized in that: In the step S2, the pressing is unidirectional pressing or bidirectional pressing.
Citation Information
Patent Citations
Production technology of hard alloy bar used for cutting machining
CN109396451A
Refractory material mixing uniformity tracer agent
CN111007045A